Glucose Metabolism and Human Immunodeficiency Virus Type 1 Infection - Zhonghe Chen; Tiantian Wang; Kai Deng (​​​​​​​​Infectious Diseases & Immunity)
Abstract. Acquired immune deficiency syndrome is still one of the most severe global infectious diseases that pose a significant threat to human health. With the successful application of antiretroviral therapy, productive replication of human immunodeficiency virus type 1 (HIV-1) can be effectively blocked; however, antiretroviral therapy alone cannot cure the infection because of the presence of a stable and reactivatable viral latent reservoir. Thus, it is of great importance to have a better comprehension of the mechanisms driving HIV-1 pathogenesis and long-term persistence in infected individuals, based on which to further discover novel targets for therapeutic applications to treat or even cure the infection. Various studies have revealed that cellular metabolism is a critical factor impacting the fate and intracellular activities of immune cells. Emerging evidence implies that the alternations of cellular metabolism induced by HIV-1 infection play an important role in HIV-1 pathogenesis. Consequently, a promising approach of “metabolism as a therapeutic target” raised the possibility of using metabolic reprogramming as a treatment option for chronic HIV-1 infection. In this review, we summarize the latest studies about the interplay of the hosts' reprogramming of glucose metabolism and HIV-1 infection and introduce potential applications of searching for hallmarks and therapeutic targets of metabolic interventions for HIV-1 infection.